Clinical Efficacy Of Bhudhatryadi Yoga In The Management Of Prameha Roga W.S.R. To Diabetes Mellitus - Badhoria, Anil; Kaundal, Ramesh (International Research Journal of Ayurveda & Yoga, 2021)
Background -In spite of all sorts of advancements of science, in this world, man is not able to sail himself in the boat of happy & healthy life. Unnatural ways of life style, increased population and moreover world of machines has created unlimited desires in human mind on the one hand, while on the other hand, it has originated anxiety, anger, hostility & grief directly or indirectly. So many diseases are there which are output of unnatural dietary habits, restless lifestyle and stress, one of such is Diabetes. The syndrome of Diabetes Mellitus is largely covered under the broad heading of Prameha. Prameha is a disease which is revealed by Mutravaha Srotasa [Urinary system]. Aim- To assess the clinical efficacy of Bhudhatryadi Yoga in in the management of Prameha Roga w.s.r. to Diabetes Mellitus Material and Method-30 Patients were selected randomly from OPD and IPD of Kayachiktisa Deptt. of Jammu Institute of Ayurveda and Research hospital. Selected patients were administered Bhudhatryadi yoga 3gm bid for a period of 45 days along with life style modifications. Weekly follow up of patients was done, while biochemical investigations were carried out before and after trial. Result-. Marked Improvement was seen in 16.66% patients. 40% of cases presented Moderate Improvement and 36.66% were categorized as Mildly Improved after the treatment. Conclusion- Bhudhatryadi yoga has better effects in reducing blood sugar level.